Manajemen dan Organisasi Informasi : Studi di Fakultas Teknologi Informasi Universitas Kristen Satya Wacana Salatiga - Albertoes Pramoekti Narendra (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This study aims to find out about the process of activities from the beginning to the end about the management and organization of information held at the Information Technology Faculty of Satya Wacana Christian University in Salatiga. This study This study used a qualitative approach using the case study method. One interesting thing to do is that in the management activities of stored information various kinds of documents result from various activities of the academic community. Documents and information held by the Information Technology Faculty are divided into 2 groups. The first group is an archival document and the second group is a library document. This research focuses on managing library documents. In implementing this management and information organization activities, the SWCU Information Technology Faculty formed a task force under the name of the Center for Documentation and Scientific Information. The main task of the task unit is to plan, carry out and make reports on the implementation of tasks. The results of this study that the organization and retrieval of information and documents using the information system diagramming framework introduced by Doyle. Some of the problems that were encountered were that the space available for this activity was incomplete and was still waiting for the purchase or procurement of various equipment to support the creation of better and more adequate information organizing activities.